2012
DOI: 10.1186/1757-4749-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-based detection of the gastrointestinal pathogen Campylobacter ureolyticus in unpasteurized milk samples from two cattle farms in Ireland

Abstract: Campylobacter jejuni and coli are collectively regarded as the most prevalent cause of bacterial foodborne illness worldwide. An emerging species, Campylobacter ureolyticus has recently been detected in patients with gastroenteritis, however, the source of this organism has, until now, remained unclear. Herein, we describe the molecular-based detection of this pathogen in bovine faeces (1/20) and unpasteurized milk (6/47) but not in poultry (chicken wings and caeca). This is, to the best of our knowledge, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Aabenhus et al (2002), Bolton et al (1987), Chaban et al (2010), Debruyne et al (2009Debruyne et al ( , 2010, Engberg et al (2000), Etoh et al (1993), Flores et al (1990), Foster et al (2004), Fox et al (1989), Garcia et al (1983), Gebhart et al (1985), Harvey and Greenwood (1985), Inglis et al (2007), Kamma et al (1999), Kaur et al (2011), Koziel et al (2012, Lastovica et al (1989Lastovica et al ( , 2006Lastovica et al ( , 2009, Lastovica and Allos (2008), Lastovica and Skirrow (2000), Lawson et al (2001), Lindblom et al (1995), Macuch and Tanner (2000), Macfarlane et al (2007), Mahendran et al (2011), Man et al (2010b, Mukhopadhya et al (2011), Nielsen et al (2013), On et al (1995a), On and Vandamme (1997), Roop II et al (1985), Rossi et al (2009), Sandstedt and Ursing (1991), Sasaki et al (2003), Stanley et al (1992), Steele et al (1985), Suzuki et al (2013), Tanner et al (1981), Taylor et al (1986…”
Section: Ecology Of Arcobactermentioning
confidence: 96%
See 1 more Smart Citation
“…Aabenhus et al (2002), Bolton et al (1987), Chaban et al (2010), Debruyne et al (2009Debruyne et al ( , 2010, Engberg et al (2000), Etoh et al (1993), Flores et al (1990), Foster et al (2004), Fox et al (1989), Garcia et al (1983), Gebhart et al (1985), Harvey and Greenwood (1985), Inglis et al (2007), Kamma et al (1999), Kaur et al (2011), Koziel et al (2012, Lastovica et al (1989Lastovica et al ( , 2006Lastovica et al ( , 2009, Lastovica and Allos (2008), Lastovica and Skirrow (2000), Lawson et al (2001), Lindblom et al (1995), Macuch and Tanner (2000), Macfarlane et al (2007), Mahendran et al (2011), Man et al (2010b, Mukhopadhya et al (2011), Nielsen et al (2013), On et al (1995a), On and Vandamme (1997), Roop II et al (1985), Rossi et al (2009), Sandstedt and Ursing (1991), Sasaki et al (2003), Stanley et al (1992), Steele et al (1985), Suzuki et al (2013), Tanner et al (1981), Taylor et al (1986…”
Section: Ecology Of Arcobactermentioning
confidence: 96%
“…They have been isolated from the feces of cats, dogs, hamsters, rodents, and cattle (Inglis and Kalischuk 2003). Shellfish, meat, and unpasteurized milk are recognized as reservoirs for these organisms (> Table 23.3, Moore et al 2006;Koziel et al 2012). C. hyointestinalis has been isolated from pigs, rusa deers, and reindeers (Hänninen et al 2002;Hill et al 1987;Gebhart et al 1985).…”
Section: Ecology Ecology Of Campylobactermentioning
confidence: 97%
“…C. ureolyticus differs from this paradigm in that it is not routinely identified (either by culture or molecular based methods) in poultry samples as demonstrated by Koziel et al, 15 a factor that may be associated with its non-thermophilic phenotype. Indeed, Koziel et al suggest that cattle as opposed to poultry are a possible reservoir 15 .…”
Section: Source Investigationmentioning
confidence: 99%
“…C. ureolyticus differs from this paradigm in that it is not routinely identified (either by culture or molecular based methods) in poultry samples as demonstrated by Koziel et al, 15 a factor that may be associated with its non-thermophilic phenotype. Indeed, Koziel et al suggest that cattle as opposed to poultry are a possible reservoir 15 . This correlates with the study by Wilson et al 4 where molecular analysis of 87 bovine samples revealed no evidence of C. ureolyticus in urine samples; however, 1 fecal sample was positive as well as 6 milk samples.…”
Section: Source Investigationmentioning
confidence: 99%
“…hyointestinalis, C. fetus subsp. fetus, C. concisus, and C. ureolyticus (384,385). Genomic analyses indicate that the presence of Campylobacter species in milk can be attributed to fecal contamination (386).…”
Section: Other Sourcesmentioning
confidence: 99%